THE LEGAL NATURE OF THE PRIVATE NURSING HOME AND NURSING HOME ELDERLY CARE CENTER ADMISSION CONTRACT IN TURKISH LAW - Aksu, Alper (PEOPLE: International Journal of Social Sciences, 2018)
Old age became a problem in modern society when we consider getting old of World population day by day. Therefore institutions emerged which take upon old people's care. With increasingly loneliness of older people and the failure to address their own needs, the importance of care which presented for them has increased. Private nursing homes and nursing home elderly care centers are one of the most important institutions involved in the care and take into account the wishes and expectations of the older people and service meet these demands and expectations are of great importance. The private nursing homes along with social reforms which in recent years have been rapidly increased in number are preferred with a view of getting better care more often than not by old people. In this study, the legal nature of the contract was examined that established between the old people who applied to the private nursing home which was referred to as the private nursing home admission contract in the doctrine and practice. The different views put forward are discussed in it. The case law on the issue has been taken into consideration in addition to the options of the doctrine on the legal nature of the acceptance contract to the private nursing home in the study. And the provisions to be applied according to the nature of the contract have been established after the legal nature of the admission contract to the private nursing home has been determined.